2010
DOI: 10.1038/onc.2010.377
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β-induced epithelial–mesenchymal transition facilitates epidermal growth factor-dependent breast cancer progression

Abstract: TGF-β and EGF play critical roles in regulating the metastasis of aggressive breast cancers, yet the impact of epithelial-mesenchymal transition (EMT) induced by TGF-β in altering the response of breast cancer cells to EGF remains unknown. We show here that murine metastatic 4T1 breast cancer cells formed compact, and dense spheroids when cultured under 3-dimensional (3D) conditions, which contrasted sharply to the branching phenotypes exhibited by their nonmetastatic counterparts. Using the human MCF10A serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
205
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(217 citation statements)
references
References 45 publications
11
205
0
1
Order By: Relevance
“…5). This cooperation has been recently reported, as TGF-b1 stimulation of EMT enabled an EGFR-driven breast cancer model to abandon its inherent branching architecture and form large, undifferentiated masses that were hyperinvasive in response to EGF (36). Interestingly, when we applied both EGF and TGF-b1 as chemoattractants, we observed the same result as when we applied TGF-b1 alone, with no spheroid formation (data not shown).…”
Section: Discussionsupporting
confidence: 87%
“…5). This cooperation has been recently reported, as TGF-b1 stimulation of EMT enabled an EGFR-driven breast cancer model to abandon its inherent branching architecture and form large, undifferentiated masses that were hyperinvasive in response to EGF (36). Interestingly, when we applied both EGF and TGF-b1 as chemoattractants, we observed the same result as when we applied TGF-b1 alone, with no spheroid formation (data not shown).…”
Section: Discussionsupporting
confidence: 87%
“…It is worth mentioning that TGFb acts as a tumor suppressor in normal tissue, but plays an oncogenic role in tumors, 32 by promoting cell growth and development of epithelial-to-mesenchymal transition. 33,34 Interestingly, in our study, we identified two different patterns of FGFR2 immunostaining: cytoplasmic and nuclear. Although cytoplasmic expression was higher in endometrial carcinoma in comparison with the adjacent atrophic endometrium from the same patients, nuclear FGFR2 FGFR2 EXON 11 These results suggest that a shift of FGFR2 from the cytoplasm to the nucleus may be associated with decreased oncogenic activity.…”
Section: Fgfr2 Mutationsmentioning
confidence: 53%
“…Importantly, transforming growth factor-b plays a pivotal role in regulating the metastasis of aggressive breast cancer cells. 19,20 We then turned to the transforming growth factor-b-controlled p38 MAPK kinase pathway. In particular, previous findings establish that p38 MAPK signaling cascades are essential for tumor invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%